Extent of pathologic extracapsular extension and outcomes in patients with nonoropharyngeal head and neck cancer treated with initial surgical resection. Issue 10 (7th February 2014) - Prabhu, Roshan S.; Hanasoge, Sheela; Magliocca, Kelly R.; Moeller, Benjamin J.; Milas, Zvonimir L.; Hall, William A.; El‐Deiry, Mark; Wadsworth, J. Trad; Higgins, Kristen A.; Beitler, Jonathan J.
Abstract : BACKGROUND: Lymph node extracapsular extension (ECE) is a known adverse prognostic factor in head and neck cancer and is an indication for adjuvant chemoradiation (CRT). However, the extent of ECE may provide additional prognostic information in the setting of adjuvant CRT. METHODS: This study included 350 patients with oral cavity cancer (72.6%) or bulky/nonfunctional laryngeal cancer (27.4%) who underwent initial surgical resection. Extent of ECE was graded from 0 to 4 based on the scale established by Lewis and colleagues. Multivariable analyses (MVA) were adjusted for primary site, pathologic risk factors, and adjuvant therapy. RESULTS: In univariate failure‐free survival (FFS) analysis, there was no significant difference in FFS for patients with lymph node‐positive disease and no ECE (grade 0) versus patients with ECE grades 1 through 3. However, patients with ECE grade 4 had significantly worse FFS. In MVA for FFS, differences between ECE grades 0 through 3 and grade 4 did not remain significant. In MVA of overall survival, ECE grade 4 was significantly associated with higher risk of death compared with ECE grade 0 (hazard ratio, 0.46; P  = .02) and ECE grades 1 through 3 (HR, 0.41; P  = .01). CONCLUSIONS: Dichotomous evaluation of ECE is useful for determining appropriate adjuvant therapy but has limited additional prognostic value in the setting of adjuvant CRT. The detrimental effect of ECE grades 1 through 3 relative to no ECE is effectively mitigated with adjuvant CRT, but ECE grade 4 retains a poorer prognosis despite CRT with regard to overall survival. Patients with ECE grade 4 may be candidates for trials investigating novel methods of adjuvant therapy intensification. Cancer 2014;120:1499–1506. © 2014 American Cancer Society . Abstract : Dichotomous evaluation (present/absent) of lymph node extracapsular extension (ECE) is useful for determining appropriate adjuvant therapy but has limited additional prognostic value in the setting of adjuvant chemoradiation (CRT) for resected head and neck cancer. With regard to overall survival, the detrimental effect of ECE grades 1 through 3 relative to no ECE is effectively mitigated with adjuvant CRT, but ECE grade 4 retains a poorer prognosis despite CRT.